Measurements of Radiofrequency Radiation with a Body-Borne Exposimeter in Swedish Schools with Wi-Fi - Hedendahl, Lena K.; Carlberg, Michael; Koppel, Tarmo; Hardell, Lennart (Frontiers in Public Health, 2017)
Introduction Wireless access to the Internet is now commonly used in schools. Many schools give each student their own laptop and utilize the laptops and wireless fidelity (Wi-Fi) connection for educational purposes. Most children also bring their own mobile phones to school. Since children are obliged by law to attend school, a safe environment is important. Lately, it has been discussed if radiofrequency (RF) radiation can have long-term adverse effects on children’s health. Method This study conducted exposimetric measurements in schools to assess RF emissions in the classroom by measuring the teachers’ RF exposure in order to approximate the children’s exposure. Teachers in grades 7–12 carried a body-borne exposimeter, EME-Spy 200, in school during 1–4 days of work. The exposimeter can measure 20 different frequency bands from 87 to 5,850 MHz. Results Eighteen teachers from seven schools participated. The mean exposure to RF radiation ranged from 1.1 to 66.1 µW/m2. The highest mean level, 396.6 µW/m2, occurred during 5 min of a lesson when the teacher let the students stream and watch YouTube videos. Maximum peaks went up to 82,857 µW/m2 from mobile phone uplink. Discussion Our measurements are in line with recent exposure studies in schools in other countries. The exposure levels varied between the different Wi-Fi systems, and if the students were allowed to use their own smartphones on the school’s Wi-Fi network or if they were connected to GSM/3G/4G base stations outside the school. An access point over the teacher’s head gave higher exposure compared with a school with a wired Internet connection for the teacher in the classroom. All values were far below International Commission on Non-Ionizing Radiation Protection’s reference values, but most mean levels measured were above the precautionary target level of 3–6 µW/m2 as proposed by the Bioinitiative Report. The length of time wireless devices are used is an essential determinant in overall exposure. Measures to minimize children’s exposure to RF radiation in school would include preferring wired connections, allowing laptops, tablets and mobile phones only in flight mode and deactivating Wi-Fi access points, when not used for learning purposes.